Saccharification of fructans and simultaneous alcoholic fermentation for sustainable production of agave distillates - Olivia A. Martínez-Aviña; Rita Miranda-López; José L. Navarrete-Bolaños (International Journal of Sustainable Engineering)
In a world where climate change and sustainability are at the forefront, innovative solutions are more pressing than ever. In the production process of distillates, the critical stage is the cooking of agave for thermal hydrolysis of fructans. This stage determines the efficiency of the process, incurs the highest production cost, and has a detrimental impact on the environment. In this study, we investigate the saccharification of agave fructans in fresh juice using fructanases produced in situ by Kluyveromyces marxianus as an alternative to traditional agave cooking. furthermore, we explore both sequential and simultaneous alcoholic fermentation processes using a native mixed culture to improve the overall yield and obtain a distillate with enjoyable sensory characteristics. The results show that saccharification and simultaneous fermentation allow for obtaining a fermented product containing an average of 7% alcohol. Gas chromatography and mass spectrometry analysis shows that the distillate is essentially an ethanol – water mixture with a broad profile and high concentration of volatile compounds. The composition of the distilled product provides a well-balanced sensory experience that is highly valued by consumers. Hence, for the first time, a novel, efficient, low-cost, and sustainable process for producing agave distillates has been successfully designed.